The Impact of Teenage Pregnancy on Maternal and Child Health: A Systematic Literature Review - Karningsih Karningsih; Endah Dian Marlina; Siti Rahmadani (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
For adolescent girls aged 15–19 around the world, complications from pregnancy and childbirth are the main cause of death. With girls under 15 being up to five times more likely to pass during delivery, this group has substantially more hazards than older women. Contributions include physical maturity, insufficient prenatal care, and socioeconomic obstacles. Correcting these inequalities is essential to raise maternal and teen health results worldwide. Adolescent mothers have a higher risk of problems including preterm birth, anemia, and preeclampsia. Their babies are more prone to have low birth weight, developmental delays, and greater death rates. Socially, teenage mothers sometimes face stigma, limited educational and job prospects, and economic hardship, therefore sustaining cycles of poverty and social injustice. This review aims to examine how common and serious maternal problems, like preeclampsia, anemia, and infections, are in teenage pregnancies. It also looks at serious issues for babies, such as low birth weight, preterm birth, and neonatal death. Finally, it studies the longterm health effects on both teenage mothers and their children, physical, psychological, and developmental aspects. Using keywords pertaining to teenage pregnancy and maternal and foetal health outcomes, the systematic review will include studies published in English or Indonesian from 2010 to 2023 focusing on teenage pregnancies (ages 10–19), maternal and foetal health outcomes, conduct thorough database searches using PubMed, and Google Scholar Teen mothers may struggle to meet the nutritional demands of pregnancy, leading to complications like preeclampsia, anemia, and a higher chance of cesarean births.